1995
DOI: 10.1002/elps.11501601168
|View full text |Cite
|
Sign up to set email alerts
|

Purification of wheat glutenin subunits by preparative acid and two‐dimensional electrophoresis

Abstract: Reduced alkylated glutenin subunits from wheat flour were fractionated by preparative electrophoresis at acid pH. The high molecular weight glutenin subunits (HMW-GS) and some of the low molecular weight glutenin subunits (LMW-GS) were purified by this one-step procedure, whereas the remainder of the LMW-GS, comigrating in the acid system, were purified in a second step by electroendosmotic preparative electrophoresis in the presence of sodium dodecyl sulfate. The quantities of recovered protein were sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Optimization of A-PAGE Preparative Fractionation of Gliadins. According to preliminary observations and in agreement with the literature (Curioni et al, 1995), the preparative system resolution was highly dependent on the separation gel length. It was found that using gels 5 cm in length, a separation of the whole gliadin fraction could be achieved.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Optimization of A-PAGE Preparative Fractionation of Gliadins. According to preliminary observations and in agreement with the literature (Curioni et al, 1995), the preparative system resolution was highly dependent on the separation gel length. It was found that using gels 5 cm in length, a separation of the whole gliadin fraction could be achieved.…”
Section: Resultssupporting
confidence: 88%
“…Regarding the purifica-tion of wheat storage proteins, Curioni et al (1989) described the use of an electroendosmotic preparative electrophoretic method to separate high molecular weight (HMW) glutenins, performing the separation under denaturing conditions at pH 8.3 in the presence of sodium dodecylsulfate (SDS). Curioni et al (1995) described a method for separation of HMW and LMW glutenins using preparative electrophoresis at acid pH.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the separation of some reduced, alkylated LMW-GS in a one-step procedure using preparative acid PAGE was described (Curioni et al 1995). This method is attractive as it involves minimal manipulation but uses alkylation of the subunits which alters their functionality in mixing studies.…”
Section: Preparative Electrophoresis and Isoelectric Focusingmentioning
confidence: 99%
“…There is evidence for the particular mildness of native electrophoresis in the fractionation of photosynthetic complexes (vs. a combination of density-gradient centrifugation with ion-exchange chromatography [298] or solely chromatography [299]). For some proteins, chromatography provides insufficient resolution, while the electrophoretic separation succeeds in a preparative scale [300,301]. Chromatographic, density gradient and electrophoretic approaches have been applied to the preparative isolation of respirasomes (see Section 4.1).…”
Section: Methods Comparison and Limitations Of Preparative Electrophormentioning
confidence: 99%